Photochemical α-selective radical ring-opening reactions of 1,3-disubstituted acyl bicyclobutanes with alkyl halides: modular access to functionalized cyclobutenes - Xiao, Yuanjiu; Xu, Tong-Tong; Zhou, Jin-Lan; Wu, Feng; Tang, Lei; Liu, Ruo-Yi; Wu, Wen-Biao; Feng, Jian-Jun (Chemical science (Cambridge), 2023)
Although ring-opening reactions of bicyclobutanes bearing electron-withdrawing groups, typically with β-selectivity, have evolved as a powerful platform for synthesis of cyclobutanes, their application in the synthesis of cyclobutenes remains underdeveloped. Here, a novel visible light induced α-selective radical ring-opening reaction of 1,3-disubstituted acyl bicyclobutanes with alkyl radical precursors for the synthesis of functionalized cyclobutenes is described. In particular, primary, secondary, and tertiary alkyl halides are all suitable substrates for this photocatalytic transformation, providing ready access to cyclobutenes with a single all-carbon quaternary center, or with two contiguous centers under mild reaction conditions. A protocol for synthesis of cyclobutenes through visible light initiated α-selective radical ring-opening of bicyclobutanes with alkyl radicals was achieved.